Critically short telomeres derepress retrotransposons to promote genome instability in embryonic stem cells - Nannan Zhao; Guoxing Yin; Chun Liu; Weiyu Zhang; Yang Shen; Dan Wang; Zhenzhen Lin; Jiao Yang; Jian Mao; Renpeng Guo; Yongwang Zhang; Feng Wang; et al. (Cell Discovery, 2023)
Abstract Telomeres, at the ends of chromosomes, protect chromosomes from fusion and preserve genomic stability. However, the molecular mechanisms underlying telomere attrition-induced genome instability remain to be understood. We systematically analyzed the expression of retrotransposons and performed genomic sequencing of different cell and tissue types with telomeres of varying lengths due to telomerase deficiency. We found that critically short telomeres altered retrotransposon activity to promote genomic instability in mouse embryonic stem cells, as evidenced by elevated numbers of single nucleotide variants, indels and copy number variations (CNVs). Transpositions of retrotransposons such as LINE1 resulting from the short telomeres can also be found in these genomes with elevated number of mutations and CNVs. Retrotransposon activation is linked to increased chromatin accessibility, and reduced heterochromatin abundance correlates with short telomeres. Re-elongation of telomeres upon recovery of telomerase partly represses retrotransposons and heterochromatin accumulation. Together, our findings suggest a potential mechanism by which telomeres maintain genomic stability by suppressing chromatin accessibility and retrotransposon activity.